Opportunity NYC: A performance-based conditional cash transfer programme. A quantitative analysis - Michelle Morais de Sá e Silva (International Poverty Centre (IPC), 2008)
As one of the first pieces of published research on New York's conditional cash transfer (CCT) programme, this paper presents the nuts-and-bolts of Opportunity New York City. It details the programme's performance-based conditionalities, contrasts its different subcomponents, and compares its design and conception to that of its precursor CCT programmes in Latin America. Finally, the paper considers whether Opportunity NYC will be able to harness broad political support in the city and become an enduring solution to education reform in the largest public school system in the United States. Critics of its conception and practice certainly abound.
Keywords: 330